Analyze of input process parameter variation on threshold voltage in 45nm n-channel MOSFET - Salehuddin F.; Ahmad I.; Hamid F.A.; Zaharim A.; Elgomati H.A.; Majlis B.Y. (2023)
In this paper, Taguchi method was used to analyze of input process parameters variations on threshold voltage (V TH) in 45nm n-channel Metal Oxide Semiconductor device. The orthogonal array, the signal-to-noise ratio, and analysis of variance are employed to study the performance characteristics of a device. In this paper, there are eight process parameters (control factors) were varied for 2 and 3 levels to performed 18 experiments. Whereas, the two noise factors were varied for 2 levels to get four readings of VTH for every row of experiment. VTH results were used as the evaluation variable. This work was done using TCAD simulator, consisting of a process simulator, ATHENA and device simulator, ATLAS. These two simulators were combined with Taguchi method to aid in design and optimize the process parameters. In this research, S/D implant energy was identified as one of the process parameter that has the strongest effect on the response characteristics. While the halo implant dose was identified as an adjustment factor to get the nominal values of VTH for NMOS device equal to 0.289V at tox 1.06nm. 2011 IEEE.